Pengaruh Keberadaan Dapur Setiap Outlet dalam Menunjang Kelancaran Pelayanan di Food & Beverage Department, The Rich Jogja Hotel - Supriyanto, Slamet; Prasasti, Ajeng Sonya Citra; Yulianto, Gunawan (Journal of Tourism and Creativity, 2023)
ABSTRACT The Rich Jogja Hotel seeks to maximize service in this case services related to products produced by the kitchen according to the outlets owned to satisfy guests. With these problems, research is carried out using qualitative research methods, where this research is carried out by collecting data based on research including observation, documentation, data analysis and literature review from various sources. The success of kitchen services at each outlet will be supported by the presence of a kitchen in each outlet itself, its location, and staff who participate in carrying out tasks based on responsibilities. Keywords: Kitchen, service, human resources